Efektivitas Penyaluran Bantuan Langsung Tunai (BLT) Dana Desa di Kecamatan Sembakung - Hasyim; Agus Prastyawan; Dandan Haryono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to describe and analyze the effectiveness of the distribution of Village Fund Direct Cash Assistance (BLT) in Sembakung District, Nunukan Regency as well as supporting and inhibiting factors in implementing the program. This research uses a qualitative descriptive research design (positivism) with a quasi-qualittaive format (quasi-qualitative or pseudo-qualitative design). In the data collection process, this research used interview methods and literature/documentary studies to obtain an overview regarding the implementation of the effectiveness of Village Fund Direct Cash Assistance (BLT) distribution in Sembakung District, Nunukan Regency. This research uses the effectiveness theory proposed by Budiani to measure the extent of the effectiveness of this program using 4 (four) dimensions, namely target accuracy, socialization, goal achievement and program monitoring. The results of this research indicate that the implementation of the effectiveness of the distribution of Village Fund Direct Cash Assistance (BLT) in Sembakung District, Nunukan Regency is running effectively. However, in its implementation there are still several problems, especially in compliance and on target. For this reason, it is necessary to synchronize data and continue monitoring by the government in implementing the BLT-DD program.